An Alternate Proof of the De Branges Theorem on Canonical Systems. (3rd April 2014) - Acharya, Keshav Raj
Abstract : The aim of this paper is to show that, in the limit circle case, the defect index of a symmetric relation induced by canonical systems, is constant on ℂ . This provides an alternative proof of the De Branges theorem that the canonical systems with tr   H 1 imply the limit point case. To this end, we discuss the spectral theory of a linear relation induced by a canonical system.